Strains and stresses in coordination compounds - Comba, Peter (Coordination chemistry reviews, 1999)
The possible ways to induce strain in coordination compounds and the quantification of steric effects and their influence on molecular properties are discussed. Based on various specific examples, including cobalt(III), cobalt(II), iron(III) and iron(II) hexaamines and copper(II) and copper(I) tetraamines, observed and computed structural data are used to analyze the effects of extremely short and long bonds and of severe angular distortions on reactivities, complex stabilities, electronic and EPR spectra and reduction potentials. Methods that allow the prediction of these molecular properties, based on experimentally determined or computed structures, are described in detail.